Kejadian Hiperbilirubin pada Bayi di Ruang Vinolia RS Pertamina Balikpapan: Hyperbilirubinemia Incident in Infants in the Vinolia Room of Pertamina Balikpapan Hospital - Novitasari, Ika Agustina; Sofiyanti, Ida (Universitas Ngudi waluyo, 2025)
Hyperbilirubinemia is the excessive accumulation of bilirubin in the blood and is characterised by jaundice. Hyperbilirubinemia in neonates can be obvious if the bilirubin level in the blood is more than or equal to 5 mg/dl. The results of a preliminary study at Pertamina Balikpapan Hospital, it was found that the number of newborns for the January– August 2023 period was 358. Meanwhile, the number of newborns with hyperbilirubin was 76 (21.2%). This research aims to find out the description of the incidence of hyperbilirubin in babies in the Vinolia Room at Pertamina Hospital Balikpapan. This type of research uses quantitative research with a descriptive research design. The research population was all newborn babies with hyperbilirubinemia in the Vinolia Room at Pertamina Hospital Balikpapan, and the sampling technique used was a total sampling of 76 people. Data collection uses data collection format sheet. Data analysisis a univariate analysis using a percentage frequency distribution test. The description of the incidence of hyperbilirubi in babies based on characteristics mostly occurs in male gender as manyas 40 people (52.6%) andgestational age < 37 weeks as many as 53 people (69.7%). The description of ABO incompatibility in babies was mostly found in the yes category, namely 51 people (67.1%). The description of low birth weight in babies was mostly found in the yes category, namely 50 people (65.8%). Most of the descriptions of prematurity in babies were in the yes category, namely 53 people (69.7%). The description of the type of delivery for babies was mostly found in the artificial category, namely 59 people (77.6%). Based on research results, the majority of cases of hyperbilirubin in babies at Pertamina Balikpapan Hospital are pathological hyperbilirubin. Abstrak Hiperbilirubinemia adalah akumulasi bilirubin dalam darah yang berlebihan, ditandai dengan adanya jaundice atau ikterus. Hiperbilirubinemia pada neonatus dapat terlihat nyata jika kadar bilirubin dalam darah lebih dari atau sama dengan 5 mg/dl. Hasil studi pendahuluan di RS Pertamina Balikpapan didapatkan jumlah bayi baru lahir periode Januari-Agustus 2023 sebanyak 358 bayi. Sedangkan jumlah bayi baru lahir dengan hiperbilirubin sebanyak 76 bayi (21,2%). Penelitiаn ini bertujuаn untuk mengetаhui gambaran kejadian hiperbilirubin pada bayi di Ruang Vinolia RS Pertamina Balikpapan. Jenis penelitiаn menggunаkаn penelitiаn kuаntitаtif dengаn desаin penelitiаn deskriptif. Populаsi penelitiаn аdаlаh seluruh bayi dengan hiperbilirubinemia di Ruang Vinolia RS Pertamina Balikpapan dаn teknik pengаmbilаn sаmpel menggunаkаn total sаmpling sebаnyаk 76 orаng. Pengumpulаn dаtа menggunаkаn lembar format pengumpulan data. Аnаlisis dаtа аdаlаh аnаlisis univаriаt menggunаkаn uji distribusi frekuensi. Gambaran kejadian hiperbilirubin pada bayi berdasarkan karakteristik banyak terjadi pada jenis kelamin kelamin laki-laki sebanyak 40 orang (52,6%) dan usia kehamilan < 37 minggu sebanyak 53 orang (69,7%). Gambaran inkompatibilitas ABO pada bayi didapatkan sebagian besar dengan kategori ya sebesar 51 orang (67,1%). Gambaran berat badan lahir rendah pada bayi didapatkan sebagian besar dengan kategori ya sebesar 50 orang (65,8%). Gambaran prematuritas pada bayi didapatkan sebagian besar dengan kategori ya sebesar 53 orang (69,7%). Gambaran jenis persalinan pada bayi didapatkan sebagian besar dengan kategori buatan yaitu 59 orang (77,6%). Berdasarkan hasil penelitian mayoritas kejadian hiperbilirubin di RS Pertamina Balikpapan yaitu hiperbilirubin patologis.